Epidemiology and Risk Factors of Alzheimer's Disease in Iran: A Systematic Review - Elham NAVIPOUR; Mahbobeh NEAMATSHAHI; Zahra BARABADI; Mohammad NEAMATSHAHI; Aghilallah KEYKHOSRAVI (Tehran University of Medical Sciences, 2019)
Background: Alzheimer's disease is a chronic disease characterized by a progressive decline in mental abilities and quality of life alongside behavioral abnormalities associated with high economic burden. The purpose of this study was to investigate epidemiology and risk factors of Alzheimer's disease in Iran. Methods: In this systematic review study, both Persian and English-language databases including Medline, Google Scholar, PubMed, web of science and Magiran were searched using following keywords: epidemiology, Alzheimer, dementia and Iran without time limit up to 2017. Thirty articles abstract out of 50 studies related to this topics, were reviewed. Of which 12 full text entered into the quality assessment process and finally, four articles were selected for inclusion in this study and their results was extracted. Results: The total sample size of the 4 selected studies was 2781. The prevalence of Alzheimer's disease in the current study was estimated to be 2.3% in the population of 67-78 years old. Age, genetics, depression and hypertension were determined as the risk factors for Alzheimer's disease, while daily listening to music, meeting weekly with friends and daily intake of vitamin E were considered as the factors with protective role in this disease. Conclusion: Alzheimer's disease is one of the main causes of functional dependence and mortality in the elderly people. Lifestyle changes and multiple mental activities in elderly increases the cognitive ability of these population, which will reduce direct and indirect costs of this disease.